Estudio de la satisfacción de los visitantes para la mejora de la oferta turística en el destino Manta - Mendoza Ocampo, Gema Yadira (2020)
The objective of this research was to study the satisfaction of tourists visiting the Manta destination. After the study, proposals for strategies were designed that will contribute to improving the offer of tourist services in the destination. The research was mixed with a descriptive approach, where the execution of the same 3 phases was proposed, which began with a diagnosis of the canton, where tools and instruments were used to collect bibliographic information. Also, the destination's supply and demand were analyzed taking into account variables for the development of the aforementioned activity. In the second phase, the structure of consumption of goods and services was analyzed to find out the average expenditure of each tourist concerning the existing offer. After the activity carried out, the satisfaction of demand was measured using the survey validated in the HOTELQUAL model. In the third phase, the proposal of strategies was considered based on the deficiencies which negatively affected the service and therefore nine strategies were established, among which stand out; update the knowledge of the operating personnel following the trends that have arisen in the tourist activity and implement tools that allow knowing the tastes and preferences of the demand, and design products and services according to the needs of the demand.